Anemia in Pediatric Inflammatory Bowel Disease. Issue 3 (September 2018) - Aljomah, Ghanim; Baker, Susan S.; Schmidt, Kenneth; Alkhouri, Razan; Kozielski, Rafal; Zhu, Lixin; Baker, Robert D.
ABSTRACT: Objectives: Anemia is the most frequent extra-intestinal finding in inflammatory bowel disease (IBD). The aim of this study is to determine the prevalence and types of anemia in pediatric patients with IBD at diagnosis and at approximately 1 year follow-up. Methods: This is a retrospective chart review of patients diagnosed with IBD from 2005 to 2012, ages 1 to 18 years. Patients who had hemoglobin, hematocrit, mean corpuscular volume, and iron indices obtained at the time of diagnosis and at approximately 1 year follow-up were included in the study. The prevalence of anemia at the beginning and the end of the study was recorded. Using the soluble transferrin receptor index the type of anemia was determined. Results: At diagnosis, 67.31% of patients were anemic. Overall, 28.85% of patients had either iron deficiency anemia (IDA) or a combination of IDA and anemia of chronic disease (ACD), whereas 38.46% had ACD alone. At follow-up, 20.51% were anemic. 15.38% had either IDA or a combination of IDA and ACD; 5.13% had ACD alone. The pattern of anemia and response to therapy differed among the IBD phenotypes Conclusions: Anemia is frequent in inflammatory bowel disease. The prevalence was higher in Crohn disease (CD). At 1 year, the prevalence of anemia decreased significantly, but persisted. Anemia of chronic disease predominated in CD. Iron deficiency anemia continued to be present in CD and ulcerative colitis. Abstract : Supplemental Digital Content is available in the text